GEOMORFOLOGI DAN MORFOMETRI DAERAH ALIRAN SUNGAI (DAS) TINALAH DI KABUPATEN KULONPROGO DAERAH ISTIMEWA YOGYAKARTA - Septian Vienastra (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2018)
Tinalah Watershed is part of the Progo Sub-watershed. The Tinalah River flows to southeast and its outlet on the Progo River. Tinalah Watershed has a ​​resource that has not been utilized optimally, road network is good enough, there are farms and plantation. Parameters that measured and analyzed include geomorphological conditions and calculation of morphometric variables. Geomorphological conditions in this watersheds most of them are hills stretching from north to south with varying degrees of erosion. Landform in this watershed Tinalah form of the origin of fluvial, structural, and denudational process. Based on the calculation of watershed morphometric the following results are obtained: Area watershed (A) of 44.43 km2. The number of River Order (Nu) in each river order from 1 to 5 respectively is 136, 25, 8, 2, and 1. Bifurcation Ratio (Rb) at each order of the order ranging from 1 to 4 respectively is 5.44; 3,125; 4 and 2. Circulatioan Ratio (Rc) value is 0,558. Main river length (L) is 13.02 km, River Density (Dd) 2.77 km / km2, Length and Wide of Watershed 11.05 km and 5.44 km. The value of the river slope (Sb) is 6.8% and the Slope of Watershed (So) is 43%.